Enjoyment in Sport and Alcohol Use among Adolescents: Examining the Mediating Role of Engagement - Schmidt, Vanina Ines (2024)
Background: Alcohol consumption among young people is a significant public health concern. Previous studies have indicated that participation in sports, through the positive experiences it offers, may function as a protective factor for alcohol intake. This study aims to examine the influence of enjoyment and personal fulfillment on adolescent alcohol use, exploring the role of engagement with sports as a mediating variable. Method: A total of 370 adolescents (Mean age = 15.08; SD = 1.48) participated in the study and completed the Alcohol Use Disorder Identification Test, the Enjoyment in Sports Scale, and the Athlete Engagement Questionnaire. Results: The results demonstrated that enjoyment is related to lower alcohol consumption through personal fulfillment and engagement in the activity. Conclusions: It is crucial to facilitate positive experiences in sport that promote engagement and generate a sense of personal fulfillment, as these factors may reduce the likelihood of risky alcohol consumption.